2022
DOI: 10.3390/jcm11041088
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thrombocytopenia as a Manifestation of COVID-19 Infection

Abstract: Clinical manifestations of COVID-19 infection can range from an asymptomatic clinical form to acute respiratory distress depending on the virus gateway, viral load, host immunity, and existing comorbidities. Some patients with COVID-19 infection can present hematological changes depending on the patient’s immune response and the severity of the infection. We present two different manifestations of thrombotic disorders related to COVID-19: one severe form of immune thrombocytopenia in a young woman with no como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…In our study, we excluded patients with COVID-19 to match the inclusion criteria of a previous similar study by Han,et al [6]. This was also because COVID-19 has been linked to thrombocytopenia of varying degrees, as reported in previous studies, case reports, and case series [19,[31][32][33][34][35][36][37][38]. Thus, we wanted to exclude this condition as a potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we excluded patients with COVID-19 to match the inclusion criteria of a previous similar study by Han,et al [6]. This was also because COVID-19 has been linked to thrombocytopenia of varying degrees, as reported in previous studies, case reports, and case series [19,[31][32][33][34][35][36][37][38]. Thus, we wanted to exclude this condition as a potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet transfusion is often considered in patients with severe thrombocytopenia to prevent bleeding complications [ 19 ]. Our study found a significant association between platelet transfusion and the degree of thrombocytopenia, organ dysfunction, shock, and third space loss [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia has also been identified as a clinical manifestation of COVID-19 in half of the patients, and in almost 95% of cases the condition was found to be serious [32]. However, bleeding is rare even in the presence of DIC with thrombocytopenia.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%